AI-driven personalized athletic interventions: impact of the NExGEN prompt generator–ChatGPT on dietary and physical training adherence and endurance performance in team sport athletes / Syaza Hazwani Manan ... [et al.]. - Manan, Syaza Hazwani; Mohd Dan, Azwa Suraya; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines the integration of the novel prompt generator, NExGEN, and ChatGPT on dietary and physical training adherence among team sport athletes over three months [1]. The research also evaluates changes in intermittent endurance performance using the Yo-Yo Intermittent Recovery Test Level 1 [2]. The study explores AI-driven models for personalized interventions, targeting gaps in prompt quality and chatbot efficacy in athletic dietary and physical training recommendations. The study recruited 21 team sport athletes (12 males, 9 females, aged 18–29 years) from Universiti Teknologi MARA. Participants completed a Physical Activity Readiness Questionnaire and baseline fitness tests, including the Yo-Yo Intermittent Recovery Test Level 1 [3]. Dietary adherence was scored weekly using Nutritionist Pro™, and NExGEN-ChatGPT tailored diet and exercise plans based on athlete-specific data, continuously refined using real-time feedback over three months.